15-year follow-up of MoM 36-mm THA: clinical, laboratory, and radiological (CT and MRI) prospective assessment. Issue 2 (December 2020) - Bozza, Nicola; Guindani, Nicola; Pezzotta, Giuseppe; Alberto, Ferrari; Castelli, Claudio C
Introduction: There is limited knowledge of the long-term results of metal-on-metal total hip arthroplasty (MoM THA), particularly concerning adverse local tissue reaction (ALTR), Co/Cr ions level and revision rate. Even if MoM bearing surfaces are no longer used, long-term data could help in defining the course and best management for these patients. The purpose of this study is to investigate the clinical outcomes, describe radiological findings including CT metal artefact reduction algorithm for orthopaedic implants (O-MAR) and MRI multi acquisition variable resonance image combination (MAVRIC) in 36-mm MoM THA. Methods: In this long-term prospective study, 46 consecutive patients with primary MoM THA (mono- or bilateral) were enrolled between 2004 and 2005. Pinnacle acetabular cup, Summit cementless stem with 36-mm metal head and Ultamet CoCr alloy liner (Depuy Inc.) were implanted, in the same centre by the same senior surgeon. Patients were reviewed at 5-, 10- and 15-years, including Co/Cr levels and standard radiographs at every follow-up, whilst the 15-year follow-up included hip sonography, MRI MAVRIC and CT O-MAR. Results: At 15 years, the overall survival rate of the implants (both stems and cups) was 83% (30/36). Revisions were performed in 9% (4/46) because of ALTR, 2% (1/46) septic loosening and 2% periprosthetic fracture. Both Cr and Co concentration increased over time, even though remaining at low level risk at 15 years: Co from 0.11 (+/– 0.18) to 4.29 (+/– 3.26) and Cr from 0.38 (+/– 0.32) to 1.37 (+/– 1.15). Functional scores in non-revised patients showed good to excellent results in more than 90%. Engh-score correlated with time from surgery ( p = 0.017) and with sonographic, CT and RM findings ( p < 0.05). Concordance has been found between CT and MRI findings (sign-rank test, p = 0.241; Intraclass Correlation Coefficients 0.987); however, no specific MRI or CT lesion patterns could be recognised among symptomatic and non-symptomatic patients. Discussion: The long-term rate of ALTR after 36-mm MoM THA was comparable with previous studies; a regular follow-up for those implants is mandatory. During follow-up Co-Cr levels increased over time and radiography was a suitable screening technique; the Engh score in particular, proved to be a reliable assessment tool. CT O-MAR and MRI with MAVRIC protocols may add valuable data in clinical practice, although MRI is significantly more efficient than CT in the identification of ALTR lesions, peri-articular effusion and in the evaluation of soft tissues.